Aluminium Interdigitated Electrode Based Biosensor for Specific ssDNA Target Listeria Detection. Issue 1 (February 2020) - Afnan Uda, M. N.; Jambek, Asral Bahari; Hashim, U.; Uda, M. N. A.; Bahrin, M. A. F.
Abstract: Nowadays interdigitated electrode (IDE) based sensor have stimulated increasing interest in the application of biosensor filed. A large number of finger electrodes as comb structure gain high sensitivity through electrical measurements. In this paper, we have investigated Listeria bacteria detection through the electrical based IDE. Listeria monocytogenes is a food borne pathogen-based bacterium that can cause dangerous disease to human, some infection may result in death. The AutoCAD software was used to design the chrome mask of IDE sensor and the fabrication process was done using conventional photolithography method. The fabricated Al IDE morphologically analyzed using a low power microscope (LPM), a high-power microscope (HPM) and 3D profiler. Functionalization step of the Al IDE, silanization process was done using (3-Aminopropyl) triethoxysilane (APTES), immobilization process was done using carboxylic probe Listeria and Tween-20 as a blocking agent for nonspecific binding on the non-immobilized area of the biosensor surface. The biosensor was validated with complementary, non-complementary and single base mismatch ssDNA targets. Different concentration of complementary ssDNA target from 1 fM to 1 µM was done for the sensitivity detection.